Venetoclax in relapsed or refractory chronic lymphocytic leukaemia with 17p deletion: a multicentre, open-label, phase 2 study. Issue 6 (June 2016) - Stilgenbauer, Stephan; Eichhorst, Barbara; Schetelig, Johannes; Coutre, Steven; Seymour, John F; Munir, Talha; Puvvada, Soham D; Wendtner, Clemens-Martin; Roberts, Andrew W; Jurczak, Wojciech; Mulligan, Stephen P; Böttcher, Sebastian; et al.
Summary: Background: Deletion of chromosome 17p (del[17p]) in patients with chronic lymphocytic leukaemia confers very poor prognosis when treated with standard chemo-immunotherapy. Venetoclax is an oral small-molecule BCL2 inhibitor that induces chronic lymphocytic leukaemia cell apoptosis. In a previous first-in-human study of venetoclax, 77% of patients with relapsed or refractory chronic lymphocytic leukaemia achieved an overall response. Here we aimed to assess the activity and safety of venetoclax monotherapy in patients with relapsed or refractory del(17p) chronic lymphocytic leukaemia. Methods: In this phase 2, single-arm, multicentre study, we recruited patients aged 18 years and older with del(17p) relapsed or refractory chronic lymphocytic leukaemia (as defined by 2008 Modified International Workshop on Chronic Lymphocytic Leukemia guidelines) from 31 centres in the USA, Canada, UK, Germany, Poland, and Australia. Patients started once daily venetoclax with a weekly dose ramp-up schedule (20, 50, 100, 200, 400 mg) over 4–5 weeks. Patients were then given daily 400 mg continuous dosing until disease progression or discontinuation for another reason. The primary endpoint was the proportion of patients achieving an overall response, assessed by an independent review committee. Activity and safety analyses included all patients who received at least one dose of study drug (per protocol). This study is registered with ClinicalTrials.gov, number NCT01889186 . Follow-up is ongoing, and patients are still receiving treatment. Findings: Between May 27, 2013, and June 27, 2014, 107 patients were enrolled into the study. At a median follow-up of 12·1 months (IQR 10·1–14·2), an overall response by independent review was achieved in 85 (79·4%; 95% CI 70·5–86·6) of 107 patients. The most common grade 3–4 adverse events were neutropenia (43 [40%]), infection (21 [20%]), anaemia (19 [18%]), and thrombocytopenia (16 [15%]). Serious adverse events occurred in 59 (55%) patients, irrespective of their relationship to treatment, with the most common (≥5% of patients) being pyrexia and autoimmune haemolytic anaemia (seven [7%] each), pneumonia (six [6%]), and febrile neutropenia (five [5%]). 11 patients died in the study within 30 days of the last dose of venetoclax; seven due to disease progression and four from an adverse event (none assessed as treatment related). Interpretation: Results of this trial show that venetoclax monotherapy is active and well tolerated in patients with relapsed or refractory del(17p) chronic lymphocytic leukaemia, providing a new therapeutic option for this very poor prognosis population. Additionally, in view of the distinct mechanism-of-action of venetoclax, combinations or sequencing with other novel targeted agents should be investigated to further advance treatment of del(17p) chronic lymphocytic leukaemia. Funding: AbbVie and Genentech.